LC-MS/MS-QTOF dataset of chemical compounds detected in honey samples from Bali and Lombok, Indonesia - Fahrul Huyopa; Saeed Ullah; Huszalina Hussin; Razauden Mohamed Zulkifli; Nurul Huda; Nyoman Semadi Antara; Roswanira Abdul Wahab; Satrijo Saloko; Anak Agung Sagung Putri Risa Andriani; Che Muhammad Khairul Hisyam Ismail; Azzmer Azzar Abdul Hamid; I. Nyoman Suarsana; et al. (Elsevier Inc., 2024)
Honey production is susceptible to manipulation by unscrupulous sellers, making honey authentication crucial to prevent fraud. The process of authenticating honey often necessitates the use of various analytical techniques, such as identifying the chemicals present in honey by means of hyphenated mass spectrometry. Here, we report on the investigation of the chemical composition of three honey samples collected at two locations in Lombok and Bali by liquid chromatography mass spectrometry (LC-MS). The three datasets include information regarding compound name, mass, retention times, as well as findings from database searches. Collectively, these data afford first insights into the compositional profile of honey samples from this specific geographical area.